Governing system innovation: assisted living experiments in the UK and Norway. Issue 12 (2nd December 2017) - Bugge, Markus; Coenen, Lars; Marques, Pedro; Morgan, Kevin
ABSTRACT: Debates on how to address societal challenges have moved to the forefront of academic and policy concerns. Of particular importance is the growing awareness that to deal with issues such as ageing, it will be necessary to implement concerted efforts on technological, social, institutional or political fronts. Drawing on a number of theoretical perspectives – including socio-technical transitions and embedded state theory – the aim of this paper is to identify and understand different approaches to the governance of such system innovations by comparing state responses to assisted living in two contrasting national systems of care, namely that of the UK and Norway. Its findings highlight that state-supported and funded experimentation projects have been instrumental in designing and implementing system innovation: through their emphasis on co-design and co-creation, these projects demonstrated the value of early implementation pilots to explore the 'fit' between novel technologies and prevailing practices and institutional structures in national systems of care. Still, competition, biases or conflicting interests should not be ignored between well-established agents and institutions and experimental solutions whose efficacy remains relatively untested and which involve a combination of new technical, social, organizational and institutional solutions.